N-glycosylation of High Mobility Group Box 1 protein (HMGB1) modulates the interaction with glycyrrhizin: A molecular modeling study. (October 2020) - Vergoten, Gérard; Bailly, Christian
Graphical abstract: Highlights: The protein High Mobility Group Box 1 (HMGB1) bears 3 N-glycans essential for its nucleocytoplasmic transport. We investigated the effect of N-glycosylation of HMGB1 using molecular modelling. The sialylated bi-antennary N-glycans introduced on HMGB1 can modulate the drug-protein interaction. The N-glycans in an extended configuration significantly weaken the binding of GLR to box-B of HMGB1. Abstract: High Mobility Group Box 1 protein (HMGB1) is an abundant protein with multiple functions in cells, acting as a DNA chaperone and damage-associated molecular pattern molecule. It represents an attractive target for the treatment of inflammatory diseases and cancers. The plant natural product glycyrrhizin (GLR) is a well-characterized ligand of HMGB1 and a drug used to treat diverse liver and skin diseases. The drug is known to bind to each of the two adjacent HMG boxes of the non-glycosylated protein. In cells, HMGB1 is N-glycosylated at three asparagine residues located in boxes A and B, and these N-glycans are essential for the nucleocytoplasmic transport of the protein. But the impact of the N-glycans on drug binding is unknown. Here we have investigated the effect of the N-glycosylation of HMGB1 on its interaction with GLR using molecular modelling, after incorporation of three N-glycans on a Human HMGB1 structure (PDB code 2YRQ). Sialylated bi-antennary N-glycans were introduced on the protein and exposed in a folded or an extended conformation for the drug binding study. The docking of the drug was performed using both 18α- and 18β-epimers of GLR and the conformations and potential energy of interaction (ΔE) of the different drug-protein complexes were compared. The N-glycans do not shield the drug binding sites on boxes A and B but can modulate the drug-protein interaction, via both direct and indirect effects. The calculations indicate that binding of 18α/β-GLR to the HMG box is generally reduced when the protein is N-glycosylated vs. the non-glycosylated protein. In particular, the N-glycans in an extended configuration significantly weaken the binding of GLR to box-B. The effects of the N-glycans are mostly indirect, but in one case a direct contact with the drug, via a carbohydrate-carbohydrate interaction, was observed with 18β-GLR bound to Box-B of glycosylated HMGB1. For the first time, it is shown (at least in silico) that N-glycosylation, one of the many post-translational modifications of HMGB1, can affect drug binding.